PENGARUH MOTIVASI, KEPEMIMPINAN, DAN DIMENSI INDIVIDU TERHADAP PRESTASI KERJA GURU SMP NEGERI 3 BENDOSARI KABUPATEN SUKOHARJO - Wicaksana, Kris -; -, Lamidi - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2010)
ABSTRACT This study aims to: (1) analyze the significance of the effect of motivation on work performance, (2) analyze the significance of the influence of leadership on job performance variables, (3) To analyze the significance of individual variables influence the dimensions of job performance, (4) analyzing the independent variables (motivation leadership, individual dimension) that have a dominant influence on the performance of the teachers SMP Negeri 3 Bendosari Sukoharjo. The population in this study were all teachers SMP Negeri 3 Bendosari Sukoharjo totaling 42 people. The sampling method with census techniques. Data were collected by questionnaires and data sources are all teachers SMP Negeri 3 Bendosari. Of the 42 questionnaires given to the respondents, only 40 questionnaires were filled completely. The data obtained were processed by multiple linear regression techniques. The results of the regression analysis yields: (1) the regression equation Y = 12,915 – 0,963 X1 + 0,653 X2 + 0,666 X3, (2) t test showed: motivation significantly influence job performance; leadership variables do not significantly influence job performance; individual dimensions variable significant effect on job performance, (3) F test indicates the variables of work motivation, leadership and individual dimensions simultaneously have a significant impact on job performance. Keywords: motivation, leadership, individual dimensions, performance.